The Analysis of Road Service Level Due to Rail Crossing: A Case of Railway Cisauk Station Area, Tangerang Indonesia - Jose Andreas; Andri Irfan Rifai; Mohamad Taufik (Indonesian Journal of Multidisciplinary Science, 2022)
Transport is the key to any country's development; thus, roads, railways, airways, and waterways have been developed for rapid urbanization and mobility. Nevertheless, many cities in the world are facing uncontrolled growth in traffic volumes, one of which is congestion. Traffic congestion is one of the most severe problems in many cities worldwide. This problem is even more pronounced in developing countries due to the rapid population and economic growth. Population and economic growth promote the expansion of urban areas and the use of cars, which leads to traffic jams. The level of road service, delays, and queue length cause congestion. Therefore, this study aims to determine the level of road service due to crossing a railway plot. The method used in this study is a direct observation or survey method, which directly calculates the volume of the vehicle, the length of delay, and the actual queue length of the field. Based on the results of research conducted on the Cisauk Highway regarding the level of road service due to the closure of the train door bars, it was concluded that the Cisauk Highway obtained a Level of Service (LoS) value of 1,674, categorized as F with the definition of forced current conditions, low speed, volume above capacity, and long queues (traffic jams). The researchers also obtained the results of the most comprehensive delay survey at 18.23 of 223 seconds, with the most extended queue length of 524 meters for the Serpong direction and 267 meters for the Cisauk direction.